(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2018)
The purpose of the study was to combine the advantages of self-nanoemulsifying drug delivery systems and tablets as a conventional dosage form. Self-nanoemulsifying drug delivery system (SNEDDS) was prepared to enhance the solubility and thus oral bioavailability of sertraline. Aqueous titration method was used to prepare the liquid SNEDDS; ternary phase diagrams were constructed and based on smaller droplet size (24.8 nm), minimum viscosity (153.63 cP) and polydispersity index (0.182), higher percentage transmittance (95%) and in vitro drug release (97%), an optimum system was designated. Liquid SNEDDS was transformed into free-flowing powder by solid adsorption technique followed by compression into tablets. In vitro release of sertraline from liquid and solid SNEDDS was found to be highly significant compared to plain sertraline (p